Atrial fibrillation progression risk factors and associated cardiovascular outcome in well-phenotyped patients: data from the AF-RISK study. Issue 3 (22nd December 2019) - De With, Ruben R; Marcos, Ernaldo G; Dudink, Elton A M P; Spronk, Henri M; Crijns, Harry J G M; Rienstra, Michiel; Van Gelder, Isabelle C
Abstract: Aims: Atrial fibrillation (AF) is a progressive disease, but identifying patients at risk for AF progression is challenging. We aimed to identify factors associated with AF progression. Methods and results: Atrial fibrillation progression was assessed in 392 patients with recent-onset paroxysmal or persistent AF included in the prospective, observational, multicentre identification of a risk profile to guide atrial fibrillation (AF-RISK) study. Progression of AF was assessed by Holter monitoring and 2-week event recorder at baseline and 1-year follow-up. AF progression was defined as: (i) doubling in AF burden at 1 year compared to baseline with a minimum AF burden of 10% in paroxysmal AF; or (ii) transition from paroxysmal to persistent or permanent AF; or (iii) persistent to permanent AF. Age was 60 ± 11 years, 62% were men, and 83% had paroxysmal AF. At 1 year, 52 (13%) had AF progression (11% in paroxysmal; 26% in persistent AF). Multivariable logistic regression showed that left atrial volume [odds ratio (OR) per 10 mL 1.251, 95% confidence interval (CI) 1.078–1.450; P < 0.001], N-terminal pro-B-type natriuretic peptide (NT-proBNP; OR per standard deviation increase 1.583, 95% CI 1.099–2.281; P = 0.014), and plasminogen activator inhibitor-1 (PAI-1; OR per standard deviation increase 0.660, 95% CI 0.472–0.921; P = 0.015) were associated with AF progression. In an additional follow-up of 1.9 (0.9–3.3) years patients with AF progression developed more cardiovascular events and all-cause mortality (12.4%/year vs. 2.3%/year, P < 0.001). Conclusion: Atrial fibrillation progression occurred in 13% of patients with recent-onset AF during 1-year follow-up. Left atrial volume, NT-proBNP, and PAI-1 were associated with AF progression. Patients with AF progression had a higher event rate. Trial registration number: Clinicaltrials.gov NCT01510210.